2016
DOI: 10.1186/s40813-016-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of gonadotropin-releasing hormone analogue administered to gilts and sows on subsequent reproductive performance and piglet birth weight

Abstract: BackgroundThe present study investigated the effect of peforelin (Maprelin®), a gonadotropin-releasing hormone (GnRH) analogue, administration in gilts, primiparous and pluriparous sows in a high productive farm on sow reproductive performance and piglet quality at birth.MethodsIn a 400 sow herd, gilts, primiparous and pluriparous sows were randomly allocated to 2 groups: peforelin treated (peforelin = P-group) or no treatment (control = C-group). Animals were injected 48 h after the last altrenogest treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
(33 reference statements)
2
19
0
Order By: Relevance
“…This is in accordance to the study by Collineau et al [45], who described the profile of ‘top-farms’ in terms of low AMU and high technical performance. Direct association of the level of external biosecurity and AMU was described in Postma et al [46], where a better external biosecurity was associated with a lower AMU in pigs from birth till slaughter. This finding was confirmed in our study where a nearly significant association between the level of external biosecurity and TI 200 days ( p = 0.06) also suggest that a lower score for external biosecurity results in more antimicrobial treatments for pigs from birth till slaughter.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance to the study by Collineau et al [45], who described the profile of ‘top-farms’ in terms of low AMU and high technical performance. Direct association of the level of external biosecurity and AMU was described in Postma et al [46], where a better external biosecurity was associated with a lower AMU in pigs from birth till slaughter. This finding was confirmed in our study where a nearly significant association between the level of external biosecurity and TI 200 days ( p = 0.06) also suggest that a lower score for external biosecurity results in more antimicrobial treatments for pigs from birth till slaughter.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings make sense because if the treatment prevented umbilical infections, it also consequently decreased the need to treat leg problems. Zoric et al [ 32 ] showed that penicillin administration for lame suckling piglets was effective in treating leg problems. In contrast to our expectations, however, we found no difference in the need for medication to treat other diseases in the piglets.…”
Section: Discussionmentioning
confidence: 99%
“…This positive influence on embryonic survival and litter weight was suggested by Jourquin and Goossens (2011) and Vangroenweghe et al (2013) in litters from peforelin treated sows [18, 19]. The mortality rate of litters born to peforelin treated sows was significantly lower (14 versus 17%) and the birth weight was significantly higher (average of 1.24 versus 1.20 kg) than in litters from untreated control sows.…”
Section: Introductionmentioning
confidence: 61%
“…It was hypothesized that treatment with peforelin results in a more uniform pre-ovulatory pool, containing more competent and larger follicles to ovulate [20]. A more uniform pre-ovulatory follicle pool may result in a more uniform oocyte quality [37] and more uniformly developed embryos [38, 39], which could finally result in more uniform birth weights [8, 18, 19]. It has been shown that animals treated with peforelin, similar as in the present study, had larger preovulatory follicles than control and eCG treated animals [17, 20].…”
Section: Discussionmentioning
confidence: 99%